1987
DOI: 10.1111/j.1651-2227.1987.tb10417.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of Physical Exercise on Working Capacity and Pulmonary Function in Cystic Fibrosis

Abstract: Seven patients with cystic fibrosis aged 6 to 20 were enrolled for 30 months in a daily exercise program. After 12 months conventional chest physiotherapy was withdrawn. Patients with low initial Shwachman scores improved as regards maximal working capacity. Spirometric data and volume of trapped gas indicated opening of closed airways. We suggest that physical exercise in general should be the basis of pulmonary therapy in cystic fibrosis. Other forms of physiotherapy are advisable when hard physical exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…Despite intensive medical treatment and dietary guidance, many CF patients have a tendency not to meet their increased energy needs, and may experience abnormalities of fat free mas (FFM) deposition, and growth failure. Exercise programmes have been shown to improve exercise tolerance in adults and children with CF [1,4,20,30]. Nutritional status and exercise tolerance in CF patients are associated with prognosis and survival [6,19], and preservation of nutritional status and exercise tolerance is therefore important [12,13,25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive medical treatment and dietary guidance, many CF patients have a tendency not to meet their increased energy needs, and may experience abnormalities of fat free mas (FFM) deposition, and growth failure. Exercise programmes have been shown to improve exercise tolerance in adults and children with CF [1,4,20,30]. Nutritional status and exercise tolerance in CF patients are associated with prognosis and survival [6,19], and preservation of nutritional status and exercise tolerance is therefore important [12,13,25].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status and exercise tolerance in CF patients are associated with prognosis and survival [1,2], and their preservation is thus important [3]. Exercise programmes have been shown to improve exercise tolerance in children and adults with CF [4][5][6][7][8][9][10][11][12]. For monitoring of exercise programmes in individual patients, easy and reliable measurements of exercise capacity with correction for nutritional status are needed.…”
mentioning
confidence: 99%
“…Since the beginning of the 1980s, physiotherapy at the centre has included inhalation therapy, airway clearance therapy and physical activity/sports/exercise [16]. The airway clearance therapy has been based upon physical exercise and interspersed with huffing, in accordance with the results of an 18-month study performed at the centre in 1980-1983 [17]. The study showed equally good results as with PD + PV and huffing, but patients refused to return to the old technique.…”
mentioning
confidence: 99%